Smart toilet / Muhammad Ridzwan Abdullah, Amirah Athirah Rohazam and Nurul Atiqah Noor Hamidy - Abdullah, Muhammad Ridzwan; Rohazam, Amirah Athirah; Noor Hamidy, Nurul Atiqah (2013)
Smart Toilet uses IR sensors to detect user after finished using the toilet. The sensor is placed in the height of the user. This project makes daily life easier and more users as consumers, they do not need to flush the toilet. It will also ensure a clean toilet bowl because it automatically flushes after use. Also subsequent users more comfortable using the toilet clean of feces. IR sensor acts as an input to the PIC and we have two outputs of the LCD display and DC motors. LCD displays the process of how the system runs.